EFEKTIVITAS KURSUS CALON PENGANTIN DI KUA KECAMATAN TAGULANDANG - Yusuf, Nasruddin; Lontoh, Fawzy Moro; Tadore, Nurulhimnin (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2022)
Not all prospective brides have the knowledge and provisions related to building a harmonious household, so that many household relationships are found that do not find the purpose and meaning of a marriage. With a lack of knowledge, when dealing with conflict, the bride and groom often cannot address household issues that end in divorce. So it is necessary to provide early education about the romance of household life. This was also carried out at the KUA of Tagulandang District, Sitaro Islands Regency. Implementation of courses for prospective brides based on Regulations issued by the Director General of Islamic Community Guidance, Ministry of Religion concerning Courses for Prospective Brides No. DJ.II/491 of 2009. This Regulation of the Director General of Islamic Community Guidance is responsive and the government's concern for the high rate of divorce and domestic violence in Indonesia. This study discusses how the course of the prospective bride and groom is carried out at the KUA, Tagulandang District, Kepl. Sitaro which has been carried out for every pair of bride and groom who will carry out the wedding. Then to find out how effective the implementation of the bride and groom course is in the context of debriefing the bride and groom who will carry out the wedding. This study uses a type of research with a qualitative approach. The data collection method obtained is primary data sources, namely data from interviews with informants and participants who have attended bride-to-be courses at the KUA, Tagulandang District, Kepl. Sitaro. While other data sources, namely secondary data sources, including those that explain primary data sources, such as Perdirjen Bimas Islam No. DJ.II/491 of 2009, research results and related official documents. The results of this study concluded that it is important to hold bride and groom courses for every couple who will carry out the wedding. Even though it's not completely perfect as an inhibiting factor, at least every bridal couple is given coaching and counseling until after the wedding accompaniment.